Design and fabrication of alcohol prevention system / Muhammad Naufal Najmi Mohd Lokman - Mohd Lokman, Muhammad Naufal Najmi (2023)
The final year project consists of programming a system that preventing user from handling an automotive or a machine under the influence of alcohol. The main idea is to force the users to evaluate themselves through an inspection before driving. This project will cancel out the capability of the users to turn on their automotive's engine and force stop their engine if the users do not take the inspection intentionally. The project will provide solution to the high number of road accidents that caused by alcoholic that have taken so many innocent lives. Several research processes will be done for the success of this project which involves the circuit that should be used and the favorable data that will be used. Throughout the process, the product will be tested to ensure that it satisfies all objectives and project expectations. Several research processes will be carried out to ensure the success of this project.